A New Paradigm of Archival Science - Syarif Makmur (International Journal Labs, 2023)
Archival science as a discipline that studies the management and maintenance of archives has existed for a long time. However, with the development of information and communication technology, as well as the demands of increasingly complex information needs, the old paradigm of archival science needs to be updated. Therefore, this research was conducted to identify and explain the new paradigm of archival science that is relevant to the times. The purpose of this study is to study and analyze the dynamics of Archival Science by looking at the development and progress of Science and technology, especially information and communication technology which is growing very rapidly. The research method used is a qualitative approach through literature studies, observation and observation of archival and archival phenomena. Analysis and discussion of the phenomenon of archives and archives in Indonesia shows changes in thoughts, attitudes and behaviors of the apostolic community so that there is an anomaly, crisis and revolution in archival science towards a new paradigm of archival science, where Law number 43 of 2009 concerning Archives will undergo corrections and fundamental changes in accordance with the development of Science and Technology, especially information and communication technology that cannot be in bending. The conclusion of the results of this study is, first: there is an anomaly in archival policy. Second: there is a crisis against Law number 43 of 2009 concerning Archives which can be seen in several regions (especially Bali Province) which abolishes the Archives Service to the level of echelon III and even echelon IV. Third: there was a revolution of thought against Law number 43 of 2009 concerning Archives for immediate correction and fundamental revision.